A novel foldable stent graft - Kuribayashi, K; K. Kuribayashi (2004)
This dissertation concerns the structural design of medical stent grafts. A new type of an innovative stent graft has been developed. Unlike the conventional stent grafts which consist of a wire mesh and a covering membrane, the proposed stent graft can be made from a single folded sheet of material. Firstly, a detailed symmetric design of a foldable cylindrical tube for the new stent graft has been presented. Folding is achieved by dividing the structure into a series of identical elements with hill and valley folds as in origami (Japanese art of paper folding). The folding patterns allow the stent graft to be folded and expanded both radially and longitudinally. The relationships among the design of the elements, the number of elements in the circumferential and longitudinal directions and the folded dimensions of the stent graft have been derived. It has been found that compact folding in the radial direction can be achieved by increasing the number of circumferential elements. A geometric mismatch during deployment has also been identified. The elements have to deform when the structure is expanded. Optimum designs which minimise the deformation have been found. Secondly, a new stent graft with helical folds has also been designed to improve radial strength and ease the deployment process. Helical folds are introduced by adjusting the joining position of the two edges of a sheet that had been symmetrically jointed in the symmetric design. The relationships among the number of elements in one complete circumference of a helix, the helical angle and the radius of the helical type stent graft have been established. The locations for the helical folds are optimised for easy folding by considering both geometric aspects of folding and the buckling patterns of a thin-walled tube under torsion, which are found analytically. Thirdly, using numerical analysis of the finite element method (FEM) the strain level and overall deformation of the stent graft during deployment has been calculated. Finally, the stent graft has been manufactured to verify the concept. A number of prototypes of the stent graft, which are the same size as standard oesophageal and aortal stent grafts, have been produced successfully using the same materials as current stent grafts of stainless steel and shape memory alloy (SMA) sheets. The patterns of folds on the materials are produced by photochemical etching. It has also been demonstrated that the SMA stent grafts self-expand smoothly and gradually by a near body temperature.